ANTIFUNGAL EFFECTS OF Azadirachta indica AND OCIMUM GRATISSIMUM ON DERMATOPHYTES - Grillo, Adebayo Joseph; Ukhureigbe, Oluchi; Egwari, Louis Osayenum; Olasupo, Nurudeen Ayoade; Adeniyi, Bolanle (FUDMA Journal of Sciences, 2026)
Dermatophytes pose a global burden with a worldwide prevalence of 20 - 25%. This study was aimed at the evaluation of antifungal effects of leaf extracts of Azadirachta indica and Ocimum gratissimum on dermatophytes. Forty nine skin scrapings were obtained from patients at the Skin Disease Clinic, Lagos University Teaching Hospital Annex, Yaba.  Dermatophytes were isolated on Sabouraud dextrose agar and identified by microscopic and biochemical methods. The aqueous and ethanolic extractions of the plant leaves was done by maceration and Soxhlet method respectively. The antifungal activity was evaluated using the broth dilution method. Trichophyton mentagrophytes had the highest percentage occurrence of 43.24, followed by T. equinum (27.03), and the lowest was 5.41 for Microsporum gypseum. The aqueous extracts of both plants completely inhibited all the dermatophytes at 250mgml. The minimum inhibitory concentration (MIC) of A. indica was 125mg/ml against all the dermatophytes. However, for O. gratissimum, the MIC was 63mg/ml against T. equinum, T. verrucosum and 125 mg/ml against T. mentagrophytes. For ethanol extract of A. indica, the highest percentage reduction in radial growth (%RRG) was 94.84 at 50 mg/ml against T. equinum and the lowest %RRG was 0.33 at 5 mg/ml against E. fIoccosum. For ethanol extract of O. gratissimum, the highest %RRG was 95.71 at 50 mg/ml against T. verrucosum and the lowest was 23.6 at 5 mg/ml against M. gypseum even as E. fIoccosum was not inhibited at that concentration. The results indicated the effectiveness of studied plant extracts in controlling the growth of dermatophytes.
Keywords: Azadirachta indica; Minimum inhibitory concentration (MIC); Ocimum gratissimum; Percentage reduction in radial growth (%RRG)